Brokers, dual-role mediators and professional interpreters: a discourse-based examination of mediated speech and the roles that linguistic mediators enact. (3rd April 2017) - Hlavac, Jim
ABSTRACT: This paper presents extracts of three interactions that feature mediators with different roles: broker; dual-role mediator; professional interpreter. A discourse analysis examination employscategories of interpreter footing toshow how alignment to others indexes mediators' role-relationships. At the micro-level, analysis shows the mediators' sense of responsibility to the interaction as a social situation and to the positions and intentions of other participants. Mediators attempt to align to others in a way reflecting this, with varying consequences. The broker's agency to assume a role of indirect recapitulator of another's talk is not positively received and he re-assumes the role of responder in an intra-family dyad. The threat of breakdown in the communicative interaction compels the dual-role mediator to shift her role from reporter to non-interpreter principal. The professional interpreter provides collaborational re-presenting of talk to others retaining the role of reporter, sometimes switching to principal. Mediators' agency and awareness of macro- then micro-level features, are located in the interactions. Discussion draws on work on intercultural communicationand reflective practice that locates interpreting as acomplex ethical and political activity.